Antimicrobial Usage in Contemporary Cattle Farming: Exploring the Threat of Resistance and Strategies for Sustainable Management - et al., Pravesh Belwal (Revista Electronica de Veterinaria, 2024)
Antimicrobial resistance (AR) presents an existential threat to worldwide public health, compromising the effectiveness of clinical antimicrobial (Antimic) treatments. The spread of resistance from cattle to people by the food chain and environmental variables exacerbates this problem. The practice of cattle farming heavily depends on the use of Antimic additives in animal feed to ensure well-being and improve efficiency. In this research, we investigate the actual state of antibiotic (ABX) utilization in contemporary cattle farming. This study examines the harmful effects of AR. It explores the complex ways in which people might develop resistance through consuming animal products or exposed to contaminated surroundings, such as water, air, soil, or manure. The review emphasizes the necessity of using sustainable management measures to counteract the spread of ABX resistance in cow production. The report seeks to integrate current knowledge on the topic to achieve a complete comprehension of the situation and suggest comprehensive strategies for combat. It is crucial to prioritize the investigation of long-term alternatives and the appropriate use of Antimics in cattle to protect public health, guarantee food safety and maintain the effectiveness of Antimic treatments.